Biologi reproduksi udang mantis Cloridopsis scorpio di ekosistem mangrove Belawan, Sumatera Utara - Rivo Hasper Dimenta; Rusdi Machrizal; Khairul Khairul; Rosmidah Hasibuan; Aini Qomariah Manurung; Mahya Ihsan (Depik, 2020)
Anthropogenic activities that tend to be exploitative in the mangrove ecosystem of Belawan are thought to have an impact on the biota associated with the ecosystem. One of the impacts is thought to be implied by mantis shrimp Cloridopsis scorpio (Latreile, 1828). The reproductive biology of the shrimp is the main object that needs to be studied in relation to the impacts. This study aims to determine the distribution of gonad maturity stage, gonad somatic index, and the length of the first mature of C. scorpio in the Mangrove Ecosystem of Belawan, North Sumatera. The research was conducted on March to May 2019 with a biweekly sampling period. The purposive random sampling was applied to choose three sampling stations in the research location. Mantis shrimp samples were caught using shrimp trawl. The result showed that the gonad maturity stage of males and females were dominated by Stage I. The gonad somatic index (GSI) range of males were 7.00-10.93 and female were 7.40-11.15. The GSI value of C. scorpio is closely related to its gonad maturity development. The length of the first mature (L50) of males were 205.5010.65 mmBL and females were 186.010.48 mmBL.Keywords:Cloridopsis scorpio,Gonad maturity stage,Gonad somatic indeks,Length of the first matureABSTRAKAktivitas antropogenik yang cenderung eksploitatif di kawasan ekosistem mangrove Belawan diduga telah berdampak terhadap biota-biota yang berasosiasi dengan ekosistem tersebut. Salah satu dampaknya dialami oleh udang mantis Cloridopsis scorpio (Latreile, 1828). Aspek reproduksi C. scorpio menjadi salah satu objek yang perlu dikaji berkaitan dengan dampak tersebut. Penelitian ini bertujuan untuk menganalisis sebaran tingkat kematangan gonad (TKG), indeks kematangan gonad (IKG), dan ukuran pertama kali matang gonad (L50) dari C. scorpio di ekosistem mangrove Belawan, Sumatera Utara. Penelitian dilakukan pada bulan Maret sampai Mei 2019 dengan periode pengambilan sampel dua mingguan. Metode purposive random sampling digunakan untuk menentukan tiga stasiun pengambilan sampel di lokasi penelitian. Sampel C. scorpio ditangkap menggunakan pukat udang. Hasil penelitian menunjukkan distribusi TKG C. scorpio jantan dan betina didominasi oleh TKG I. Nilai IKG C. scorpio jantan berkisar antara 7,00-10,93 dan C. scorpio betina berkisar antara 7,40-11,15. Nilai IKG C. scorpio berkaitan dengan tahap perkembangan gonadnya. C. scorpio jantan mengalami pertama kali matang gonad (L50) pada ukuran 205,5010,65 mmBL dan C. scorpio betina pada ukuran 186,0010,48 mmBL.Kata kunci:Cloridopsis scorpio,TKG, IKG, Ukuran pertama kali matang gonad